2005
DOI: 10.1002/cne.20627
|View full text |Cite
|
Sign up to set email alerts
|

Definition and novel connections of the entopallium in the pigeon (Columba livia)

Abstract: The avian entopallium (E) is the major thalamorecipient zone, within the telencephalon, of the tectofugal visual system. Because of discrepancies concerning the structure of this nuclear mass in pigeons, and in light of recent evidence concerning entopallial projections in other avian species, we here redefine and chart some novel entopallial projections in the pigeon by using a combination of cytochrome oxidase (CO) activity, calcium binding protein immunohistochemistry (CBPi), normal histology, and tract tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
83
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 44 publications
(73 reference statements)
13
83
1
Order By: Relevance
“…In our study, this area showed a dense labeling for 5-HT 1A receptors that differed clearly from the rest of the mesopallium confirming a nuclear structure. Therefore, our findings support the idea of Krützfeldt and Wild (2005) that this area is comparable with the nucleus MVL in the zebra finch.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In our study, this area showed a dense labeling for 5-HT 1A receptors that differed clearly from the rest of the mesopallium confirming a nuclear structure. Therefore, our findings support the idea of Krützfeldt and Wild (2005) that this area is comparable with the nucleus MVL in the zebra finch.…”
Section: Discussionsupporting
confidence: 80%
“…Herein, our results support this suggestion, because layers II and III of the human extrastriate cortex also contain the highest numbers of 5-HT 1A receptors when compared with the other neocortical layers (Zilles et al, 2004;Eickhoff et al, 2007). The input region of the entopallium is the entopallial core, which can be further subdivided into an entopallium externum (Ee) and internum (Ei) (Hellmann et al, 1995;Krützfeldt and Wild, 2005). Our results in principle support such a subdivision.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Rt sends an organized projection to the entopallium, such that separate regions of the entopallium receive topographic input from different rotundal subdivisions (Laverghetta and Shimizu, 2003;Krützfeldt and Wild, 2005;Fredes et al, 2010). To determine whether the effect of the Ipc on the ascending tectal pathway extends to the entopallium, we made 74 simultaneous recordings in both structures, 36 of which were tested in a systematic way to be used for quantitative analysis.…”
Section: Synchrony Between Visual Responses In the Ipc And The Entopamentioning
confidence: 99%